2004
DOI: 10.1158/0008-5472.can-04-0389
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Potentiates the Adherence of Metastatic Prostate and Breast Cancer Cells to Bone Marrow Endothelial Cells

Abstract: The aim of this current study was to examine the significance of CD44 expression in mediating cancer cell adhesion to human bone marrow endothelial cell(s) (hBMEC). Differential CD44 expression on two metastatic prostate cancer cell lines, PC3 (CD44 ؉ve) and DU145 (CD44 ؊ve) and four breast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
178
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(198 citation statements)
references
References 28 publications
15
178
1
1
Order By: Relevance
“…In mice with PC-3 xenografts, a single intravenous treatment was not as effective as in the other two models perhaps because of higher amounts of hyaluronic acid and other matrix components. 28,29 However, tumors in PBS-treated animals were nevertheless 1.7-fold larger than in ICOVIR-7-treated animals (Po0.05) (Figure 5d) and tumors in ICOVIR-5-treated animals were 1.2-fold bigger than those in the ICOVIR-7 group (not significant). Viral replication in tumors after systemic injection of ICOVIR-7 was shown by immunohistofluorescence for adenoviral capsid proteins.…”
Section: Antitumor Efficacy Of Icovir-7 After Systemic Administrationmentioning
confidence: 85%
See 1 more Smart Citation
“…In mice with PC-3 xenografts, a single intravenous treatment was not as effective as in the other two models perhaps because of higher amounts of hyaluronic acid and other matrix components. 28,29 However, tumors in PBS-treated animals were nevertheless 1.7-fold larger than in ICOVIR-7-treated animals (Po0.05) (Figure 5d) and tumors in ICOVIR-5-treated animals were 1.2-fold bigger than those in the ICOVIR-7 group (not significant). Viral replication in tumors after systemic injection of ICOVIR-7 was shown by immunohistofluorescence for adenoviral capsid proteins.…”
Section: Antitumor Efficacy Of Icovir-7 After Systemic Administrationmentioning
confidence: 85%
“…Many tumor types are characterized by small groups of tumor cells surrounded by large areas of stroma and this may limit the intratumoral spread of viruses, especially when replication is restricted to cancer cells. 42,43 Figure 5d shows how the use of a xenograft model (PC-3) expressing high amounts of matrix components 28,29 reduces the efficacy of ICOVIR-7 with respect to other models. Arming adenoviruses with therapeutic transgenes is a rational approach to circumvent these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility certainly exists considering that CD44 has previously been implicated in facilitating PCa cell invasion in vitro (e.g. Lokeshwar et al, 1995;Draffin et al, 2004;Omara-Opyene et al, 2004). In this regard, it is of interest to note that the LAPC-9 tumors, which were initially isolated from a bony metastasis, contain many more CD44 þ cells than LAPC-4 tumors, which were originally isolated from a lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although CD44 expression is reported to be reduced in metastases (Nagabhushan et al, 1996;De Marzo et al, 1998;Noordzij et al, 1999), the CD44 þ PCa cells are found to predominate in two visceral metastases (Liu et al, 1999). Similar to expression studies, the potential role of CD44 in PCa development and metastases is controversial -although some studies show a tumor-suppressive function of CD44 in overexpression experiments (Gao et al, 1997(Gao et al, , 1998, many other studies implicate CD44 in PCa cell proliferation, adhesion, migration, and invasion in vitro as well as in metastatic dissemination in vivo (Lokeshwar et al, 1995;Paradis et al, 1998;Liu et al, 1999;Draffin et al, 2004;Omara-Opyene et al, 2004). Many studies mentioned above utilize either human tissues to carry out correlative immunohistochemistry (IHC) or bulk-cultured PCa cells to carry out overexpression experiments and the key experiment of using purified CD44 þ and CD44 À cells from the same culture or tumor to compare their potentially different biological and tumorigenic properties has not yet been done.…”
Section: Introductionmentioning
confidence: 88%
“…HA by interactions with cell surface receptors such as CD44 and receptor for hyaluronic acid (HA) is involved in cell adhesion processes [12]. The effect of HA on healthy cells has been studied extensively [13], however, little is known about HA's effect on malignant cells ex vivo.…”
Section: Introductionmentioning
confidence: 99%